A122 COMBINATION BIOLOGIC THERAPY IN INFLAMMATORY BOWEL DISEASE: THE CALGARY EXPERIENCE. (15th March 2019) - Panaccione, N; Novak, K L; Seow, C; Devlin, S; Lu, C; Heatherington, J; Kaplan, G G; Panaccione, R
Abstract: Background: Biologic therapy has revolutionized inflammatory bowel disease (IBD) care. More recently, newer biologics have been approved. Despite multiple options, clinical remission rates at one year are approximately 40% for any single biologic agent. In addition, questions surround the efficacy of newer agents in controlling extra-intestinal manifestations (EIMs). This has raised interest in whether combination biologic therapy with agents with different mechanisms of action (MOA) can be used safely to increase overall efficacy or to control EIMs. Aims: To describe the clinical experience in IBD patients treated with combination biologic therapy at the University of Calgary IBD unit. Methods: A retrospective single center cohort study was performed at the University of Calgary of IBD patients receiving combination biologic therapy. Safety and efficacy of the combination biologic therapy was assessed. Results: Ten patients (9 Crohn's disease (CD), 1 ulcerative colitis (UC)) were treated with combination biologic therapy (5M:5F). Mean follow-up was 64.8 weeks (range 10–118 weeks). All patients had failed > 3 biologics and 4/10 (40%) of patients had failed >4 previous biologics. None of the patients were started on dual biological therapy simultaneously. All patients had a biologic added to existing biologic. Primary indication to add a second biologic was medically refractory disease in 6 and control of EIMs in 4: 2 type II peripheral arthritis, 2 ankylosing spondylitis. Combinations of biologics used included: vedolizumab and adalimumab (n=3);vedolizumab and infliximab (n=3);vedolizumab and golimumab (n=2);vedolizumab and certolizumab (n=1);and ustekinumab and infliximab (n=1). Of the 6 who were on dual biologic therapy for medically refractory disease 3/6 (50%) demonstrated clinical improvement, and 3/6 (50%) demonstrated endoscopic response. Two patients (1 CD; 1 UC) underwent intestinal resection, but neither experienced a postoperative complication. The four whose primary indication was to control EIMS; anti-TNF therapy (2 adalimumab; 1 infliximab: 1golimumab) was added to vedolizumab and all patients 4/4 (100%) had complete resolution of their EIMs. One patient who had golimumab and high dose corticosteroids added to every 4 weekly vedolizumab developed a community acquired pneumonia (CAP) during the golimumab induction period. All other combinations were well tolerated during the follow-up period. Conclusions: In this small, highly selective cohort of patients with IBD, a variety of combinations of biologic therapy were well tolerated. One patient developed CAP. The combination proved to be a successful strategy to control EIMs when anti-TNF therapy was added to vedolizumab. Further studies are needed to assess the comparative efficacy of combination strategies and long term safety compared to single agents. Funding Agencies: None